Participant Activities in Favor of the Accused in Turkish and German Criminal Procedural Law - Hüsnü Sefa Eryıldız (İstanbul Hukuk Mecmuası)
The participant, who is recognized as a criminal procedure subject in Turkish and German law, is an individual prosecution subject, in contrast to the prosecutor. The participant can use the rights and powers granted by law independent of the prosecutor. Thus they have the opportunity to defend their legitimate interests and effectively influence the criminal proceedings. Whether participants can use these rights and powers in favor of the accused in proceedings is controversial in both Turkish and German law. In fact, Turkish and German criminal procedure codes have no specific regulation on the direction and purpose for which participants can use their rights and powers. Therefore, the discussion regarding the field participant activity is centered on the purpose of their participation and the conditions required for valid participation.In this regard, particularly concerning the decision of the 3rd Criminal Chamber of the German Federal Court (Decision No. 214/20 dated September 1, 2020) has added a new aspect to this debate.Although the position and activities of participants in criminal proceedings are often identified with the public prosecutor, participants are not assistants to the public prosecutor. Their clearest indicator of independence is that they have the opportunity to use their legal rights and powers independent from other judicial subjects. In this context, this study argues whether participants are allowed to exercise the rights and powers granted to them in a criminal proceeding in favor of the accused and to carry out activities for achieving this aim.This study evaluates the question of whether participants may act in favor of the accused in light of Turkish and German doctrinal views and court decisions on the subject by considering the legal regulations regarding the rights and powers granted to participants, the condition of being harmed by a crime, the purpose of participation and the condition of complaint with regard to participation. The study then examines the possibility of the participant applying for legal remedies in favor of the accused.